Early Pulmonary Lesions in Cattle Infected via Aerosolized Mycobacterium bovis. Issue 4 (July 2019) - Palmer, Mitchell V.; Wiarda, Jayne; Kanipe, Carly; Thacker, Tyler C.
Mycobacterium bovis is a serious zoonotic pathogen and the cause of tuberculosis in many mammalian species, most notably, cattle. The hallmark lesion of tuberculosis is the granuloma. It is within the developing granuloma where host and pathogen interact; therefore, it is critical to understand host-pathogen interactions at the granuloma level. Cytokines and chemokines drive cell recruitment, activity, and function and ultimately determine the success or failure of the host to control infection. In calves, early lesions (ie, 15 and 30 days) after experimental aerosol infection were examined microscopically using in situ hybridization and immunohistochemistry to demonstrate early infiltrates of CD68+ macrophages within alveoli and alveolar interstitium, as well as the presence of CD4, CD8, and γδ T cells. Unlike lesions at 15 days, lesions at 30 days after infection contained small foci of necrosis among infiltrates of macrophages, lymphocytes, neutrophils, and multinucleated giant cells and extracellular acid-fast bacilli within necrotic areas. At both time points, there was abundant expression of the chemokines CXCL9, MCP-1/CCL2, and the cytokine transforming growth factor (TGF)–β. The proinflammatory cytokines tumor necrosis factor (TNF)–α and interleukin (IL)–1β, as well as the anti-inflammatory cytokine IL-10, were expressed at moderate levels at both time points, while expression of IFN-γ was limited. These findings document the early pulmonary lesions after M. bovis infection in calves and are in general agreement with the proposed pathogenesis of tuberculosis described in laboratory animal and nonhuman primate models of tuberculosis.